Composite freeform shell structures: Design, construction and testing. (15th February 2023) - Moskaleva, Anastasiia; Gusev, Sergey; Konev, Stepan; Sergeichev, Ivan; Safonov, Alexander; Hernandez-Montes, Enrique
Abstract: Today, in modern construction practice, there is a solid interest in freeform structures and, particularly, in double curvature shells. Development of manufacturing technologies made it possible to use new, advanced materials like fiber reinforced polymers to create such structures. However, design of freeform structures with new materials will require new approaches to modeling and analysis, allowing better understanding of their structural behavior. This work is aimed at demonstrating the benefits offered by fiber reinforced polymers in freeform structures, by the example of the composite shell designed with the force density method (FDM) and topological mapping (TM). The work describes the process of form-finding, manufacturing, and mechanical testing of the shell, together with finite element analysis with account for geometric nonlinearity. In order to validate the modeling approach, the results of finite element modeling were compared with test results. The results of mechanical testing and structural analysis demonstrated the efficiency of this approach and broad prospects for composites application in freeform architecture.